The Role of Work Discipline in Mediating the Influence of Work Motivation and Stress Management on Employee Performance - Suryanto Suryanto; Tony Wijaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to determine: (1) the effect of work motivation on employee performance; (2) the effect of stres management on employee performance; (3) the effect of work discipline on employee performance; (4) the effect of work motivation on employee work discipline; (5) the effect of stres management on employee work discipline; (6) the role of work discipline in mediating the influence of work motivation on employee performance; (7) the role of work discipline in mediating the influence of stres management on employee performance. This research includes causal associative research with a quantitative approach. The population of this research is educational staff at Yogyakarta State University, all 730 educational staff at Yogyakarta State University. The sampling technique used in this research is cluster sampling (area sampling). Based on the calculation results, the sample size was 252. Data was collected using documentation and questionnaires whose validity and reliability had been tested. The data analysis technique used is path analysis using the Smart PLS 3 application. The results show that: (1) work motivation has a positive and significant effect on employee performance with a p value (0.000 < 0.05) and a t statistic value (4.737 > 1.96); (2) stress management has a positive and insignificant effect on employee performance with p value (0.058 > 0.05) and t statistic value (1.897 < 1.96); (3) work discipline has a positive and significant effect on employee performance with a p value (0.001 < 0.05) and a t statistic value (3.358 > 1.96); (4) work motivation towards employee work discipline; (5) stress management has a positive and significant effect on employee work discipline with a p value (0.000 < 0.05) and a t statistic value (5.401 > 1.96); (6) work motivation has a positive and significant indirect effect on employee performance through the mediation of work discipline with a p value (0.004 < 0.05) and a t statistic value (2.862 > 1.96); (7) stress management has a positive and significant indirect effect on employee performance through the mediation of work discipline with a p value (0.004 < 0.05) and a t statistic value (2.862 > 1.96).